2011
DOI: 10.1021/jp1122085
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Monitoring of Invertase Activity Immobilized in Nanoporous Aluminum Oxide

Abstract: In this work, we demonstrate the activity of enzyme invertase immobilized in the pores of nanoporous anodized 3 μm thick aluminum oxide (AA). The porous anodic alumina has uniform nanosized pores with an interpore distance of p = 100 nm, with pore diameters on the order of 60-65 nm. The pores trap the enzyme and continuous monitoring of the activity is carried out in a flow cell where the substrate is made to flow and the product is detected. The activity of the immobilized enzyme has been determined for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…A similar study was carried out by Koutsioubas et al [64], who characterised the adsorption and desorption of BSA onto a SPR-NAA system at different values of pH. Dhathathreyan demonstrated that this system is able to quantify real-time biological events, such as enzymatic reactions [65]. In this study, enzyme invertase was immobilised onto the nanoporous network of NAA, and its activity at different pHs and substrate concentrations was established when digesting sucrose to produce glucose and fructose.…”
Section: Optical Biosensors Based On Naamentioning
confidence: 92%
“…A similar study was carried out by Koutsioubas et al [64], who characterised the adsorption and desorption of BSA onto a SPR-NAA system at different values of pH. Dhathathreyan demonstrated that this system is able to quantify real-time biological events, such as enzymatic reactions [65]. In this study, enzyme invertase was immobilised onto the nanoporous network of NAA, and its activity at different pHs and substrate concentrations was established when digesting sucrose to produce glucose and fructose.…”
Section: Optical Biosensors Based On Naamentioning
confidence: 92%
“…[17][18][19][20] In particular, the use of nanoporous materials such as porous silicon and nanoporous anodic alumina (NAA) has resulted in several sensing systems featuring unique cutting-edge capabilities for detecting enzymes by means of different strategies. [21][22][23][24] Optical sensing platforms based on nanoporous materials can provide multiple advantages such as large specific surface area to accommodate chemically selective probes and enhance optical signals from analyte molecules, homogeneous and versatile nanoporous structure that can be engineered to create a broad range of photonic structures with precisely designed optical signals, chemical and physical stability and so forth. 25,26 The combination of gelatin-modified photonic structures based on porous silicon and reflectivity spectroscopy was introduced by Killian et al, who made a good use of this sensing concept to detect levels of metalloprotease enzyme released from stimulated human macrophage cells.…”
Section: Introductionmentioning
confidence: 99%
“…As far as the different materials used to develop optical sensing platforms is concerned, nanomaterials have enabled the development of highly sensitive and sophisticated systems such as surface enhanced Raman spectroscopy (SERS), surface plasmon resonance spectroscopy (SPR), localized surface plasmon resonance spectroscopy (LSPR) and others. [6][7][8][9][10][11][12][13][14][15] These optical techniques can achieve detection limits as low as single molecules through the amplification of 3 electromagnetic fields generated by the excitation of localized surface plasmons. 16 Another example of sensitive optical technique extensively used to develop optical sensors is reflectometric interference spectroscopy (RIfS).…”
mentioning
confidence: 99%